Lessons learned from integrated long-term monitoring of a coho salmon population complex in the Russian River watershed - Obedzinski, Mariska; Horton, Gregg E.; Nossaman Pierce, Sarah; Bartshire, Andrew; Bauer, Nicolas; Olin, Paul G.; Carlson, Stephanie M.; Grantham, Theodore E. (Frontiers in Ecology and Evolution, 2025)
In California’s Russian River watershed, home to imperiled salmon and steelhead populations, an intensive long-term monitoring program plays an integral role in supporting species recovery. The program conducts life cycle and basinwide monitoring of natural- and hatchery-origin coho salmon using PIT antenna arrays, downstream migrant traps, snorkel counts, electrofishing, and spawner surveys paired with environmental monitoring. The program has also served as a foundation for targeted research by providing baseline data and monitoring infrastructure. Long-term and consistent tracking of population metrics has indicated modest but meaningful positive trends in abundance, but has also revealed unanticipated bottlenecks to population recovery, many of which are related to low streamflow. Monitoring has also revealed complex movement patterns of juveniles and adults throughout the watershed that have broadened our understanding of salmon life history diversity and the importance of managing for diversity as a key strategy for recovering salmon. Minor adaptations to the monitoring program have enabled evaluation of specific recovery actions, including genetic intervention, flow augmentation from off-channel storage, fish passage remediation, and physical habitat restoration projects. Critical to the effectiveness of the Russian River’s monitoring program has been the ability to manage and share data through a centralized database. This has facilitated development of data dashboards that are used for management decision-making and long-term recovery planning and prioritization. We reflect on the evolution of the Russian River monitoring program, including benefits and challenges of long-term and spatially-distributed monitoring in a hatchery-supplemented population and lessons learned that have relevance for salmon recovery efforts across their range.